2017
DOI: 10.1073/pnas.1621234114
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic neural architecture for social knowledge retrieval

Abstract: Social behavior is often shaped by the rich storehouse of biographical information that we hold for other people. In our daily life, we rapidly and flexibly retrieve a host of biographical details about individuals in our social network, which often guide our decisions as we navigate complex social interactions. Even abstract traits associated with an individual, such as their political affiliation, can cue a rich cascade of person-specific knowledge. Here, we asked whether the anterior temporal lobe (ATL) ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
67
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 84 publications
6
67
1
Order By: Relevance
“…Therefore, the brain regions activated in our study and in social processing studies could be different due to different experimental tasks and contrasts. The left aSTS found here has not been reported in experiments using nonverbal person-related stimuli (e.g., human voices, faces, or biological motion; Deen, Koldewyn, Kanwisher, & Saxe, 2015) or cartoons depicting social interactions (Centelles, Assaiante, Nazarian, Anton, & Schmitz, 2011;Isik, Koldewyn, Beeler, & Kanwisher, 2017; but see Ross & Olson, 2010), either, and seems to be located posteriorly to the TP area that stores personrelated semantic knowledge (Ross & Olson, 2012;Simmons et al, 2010;Wang et al, 2017;Wang, Peelen, Han, Caramazza, & Bi, 2016).…”
Section: Sociality Effects In the Left Anterior Superior Temporal Scontrasting
confidence: 73%
See 2 more Smart Citations
“…Therefore, the brain regions activated in our study and in social processing studies could be different due to different experimental tasks and contrasts. The left aSTS found here has not been reported in experiments using nonverbal person-related stimuli (e.g., human voices, faces, or biological motion; Deen, Koldewyn, Kanwisher, & Saxe, 2015) or cartoons depicting social interactions (Centelles, Assaiante, Nazarian, Anton, & Schmitz, 2011;Isik, Koldewyn, Beeler, & Kanwisher, 2017; but see Ross & Olson, 2010), either, and seems to be located posteriorly to the TP area that stores personrelated semantic knowledge (Ross & Olson, 2012;Simmons et al, 2010;Wang et al, 2017;Wang, Peelen, Han, Caramazza, & Bi, 2016).…”
Section: Sociality Effects In the Left Anterior Superior Temporal Scontrasting
confidence: 73%
“…Note that social knowledge has been very broadly defined, from the mere presence of persons (Mellem et al, 2016;Norris, Chen, Zhu, Small, & Cacioppo, 2004), to the biographical information of specific persons (Simmons et al, 2010;Wang et al, 2017), and to socially interactive behaviors or properties (Zahn et al, 2007). Note that social knowledge has been very broadly defined, from the mere presence of persons (Mellem et al, 2016;Norris, Chen, Zhu, Small, & Cacioppo, 2004), to the biographical information of specific persons (Simmons et al, 2010;Wang et al, 2017), and to socially interactive behaviors or properties (Zahn et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al (5) asked 50 participants to learn biographical information (name, age, marital status, occupation, city of residence, and the appearance of their house as presented in a photograph) about four fictitious people over 2 d of training. On the third day, participants completed an fMRI experiment in which they were shown images of the four people's faces (pictured from different viewpoints with respect to the training), their names (written in a different font and color), their houses (pictured from different viewpoints), and images of objects associated with their occupation.…”
mentioning
confidence: 99%
“…A model in which retrieval of person knowledge represented in the IPL and PCC from perceptual cues was mediated by the ATL ("ATL as hub") was selected as optimal by Bayesian model selection, outperforming a model in which retrieval was achieved directly from representations of the perceptual cues in the FFA/WVFA, and a model in which retrieval was mediated by the hippocampus. Furthermore, using psychophysiological interactions, Wang et al (5) showed that the ATL increased its connectivity with the IPL during the retrieval of a person's status, but with the PCC during the retrieval of a person's personality traits. Multivariate pattern analyses showed that status could be decoded from the IPL (and from none of the other ROIs), and personality traits could be decoded from the PCC (and from none of the other ROIs).…”
mentioning
confidence: 99%